Respon berbagai cara pemberian konsentrat dan rumput raja terhadap pertumbuhan sapi Bali di Nimbokrang kabupaten Jayapura - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Two considerations related to feeding methods are : 1) concentrate should be given by mixing with grass together (Owen, 1979), and 2) concentrate should be given two hours before grass (Siregar, 1994). The aims of this research is to find an appropriate methods by studying the growth response of Bali cattle which given the variety of feeding methods. King Grass and concentrate composed diets comparison was 70:30 percentage. Five treatments were arrangement by Latin Square Design. This research consist of five periods by using five Bali cattle, so there are 25 experiment units. All treatments give the significance response to body weight and feed efficiency. However, King grass which given without concentrate creates better response to feed efficiency.